Undiagnosed Type 2 Diabetes Mellitus in A 68 year-old Patient with Parkinson's Disease : An Invisible Risk Factor - Fitriyani Fitriyani; Nanda Tiara Santika (Fakultas Kedokteran Universitas Lampung, 2024)
Parkinson’s Disease is a complex progressive neurodegenerative disease characterized by tremor, bradykinesia, rigidity and postural instability. PD is the second most common neurodegenerative disease after Alzheimer’s Disease, with the prevalence of 0,5-1% among the 65-69 year-old population. Diabetes mellitus is not only considered as one of the risk factors of neurodegenerative diseases, but also negatively affects cognitive functions of PD. Several mechanisms support the link between the two diseases, such as oxidative stress, mitochondria dysfunction, and neuroinflammation. A 68 year-old man, diagnosed with Parkinson’s Disease and Type 2 Diabetes Mellitus. Physical examination revealed resting tremor, bradykinesia, and rigidity. Inferior extremity was seen with solitary ulcer, 3 cm in diameter, tendon-based with pus on the ankle area; grade 2 Wagner Classification. Laboratory test revealed 271 mg/dL of random blood glucose, and 155 mg/dL of fasting blood glucose. Management included PD symptomatic agents alongside with anti-diabetic agents. Key words: Parkinson’s Disease, Type 2 Diabetes Mellitus, Case Report